Efficacy and safety of sodium-glucose cotransporter-2 inhibitors in type 2 diabetes mellitus with inadequate glycemic control on insulin: a network meta-analysis - M. V. Shestakova; G. R. Galstyan; B. B. Kvasnikov; E. E. Erina (Сахарный диабет)
The increase in the number of patients with type 2 diabetes mellitus (T2D) and mortality among them forces us to look for ways to optimize T2D treatment. At the same time, more than half of patients with an established diagnosis do not reach the glycemic targets and require intensification of therapy. Due to the progressive deterioration of the glycemic status, almost one in five T2D patients requires insulin therapy (IT), and over time, IT intensification with titration of the dose of insulin. This approach is limited by a few adverse effects such as: an increased risk of severe hypoglycemia, weight gain, decreased sodium excretion, which means fluid retention in the body, and the patient’s unwillingness to carry out complex therapy regimens. The addition of sodium-glucose cotransporter 2 (SGLT2i) inhibitor with an insulin–independent mechanism of action to the treatment is aimed to solve the problem of optimizing glycemic control in this category of T2D patients. The purpose of this network meta-analysis (NMA) was to indirectly compare the efficacy and safety of SGLT2 inhibitors added on top of insulin in T2D patients. The analysis included randomized clinical trials in which dapagliflozin, empagliflozin, ipragliflozin, luseogliflozin, and ertugliflozin were prescribed as SGLT2i. The primary endpoint was a change in glycated hemoglobin (HbA1c), and the secondary endpoints were changes in a mean of fasting plasma glucose, body weight and blood pressure, as well as the mean change in daily dose of insulin. The analysis of safety data included a comparative assessment of the incidence of hypoglycemia, reproductive tract and urogenital infections, and hypovolemia. The results of the conducted NMA demonstrate the comparable effectiveness of various SGLT2i regarding managing of glycemic status in T2D patients receiving insulin, along with commensurate safety and tolerability of therapy.